An outlook on gender equality: a demographical empirical analysis. (22nd January 2020) - Khurana, Poonam; Chhikara, Deepika
The purpose of this paper is to examine the outlook of people towards gender equality in respect to the way we behave, dress, groom, conduct and present ourselves in the society. Both primary and secondary statistics is used in this study. Primary data have been collected from respondents in Delhi, NCR by convenient random sampling with the help of self-structured questionnaire. Secondary data have been extracted from the research studies published in various reputed journals. Descriptive statistics and chi-square test (non-parametric analysis) has been used for analysis. The study shows that among all the respondents, the demography was inclined majorly towards students between the ages of 16-25 years from Delhi, the youth has evolved from the conservative approach and they treat all the gender equally. However, a significant finding of the study was that the beauty norms towards men are majorly impacted by the education level of an individual.